O-034 Carotid Artery Angioplasty versus Stenting in Acute Ischemic Stroke. (26th July 2014) - Choudhri, O; Gupta, M; Feroze, A; Albers, G; Lansberg, M; Do, H; Dodd, R; Marcellus, M; Marks, M
Abstract : Introduction: Acute ischemic stroke secondary to cervical carotid artery occlusion can lead to significant morbidity and mortality. Acute carotid occlusion may be managed by carotid angioplasty, stenting, or both. The use of carotid stents requires patients to be placed on dual antiplatelet agents, which may contribute to increased haemorrhage risk. We undertook this study to evaluate outcomes for angioplasty alone versus stenting in the setting of acute carotid occlusion. Methods: All patients treated from 2008 to 2013 with acute cervical internal carotid artery occlusions that had intervention within eight hours of symptom onset were included. NIHSS were recorded preceding intervention, and clinical outcomes were assessed using mRS at 90 days. All imaging and angiographic data were reviewed for pre-procedural ASPECT scores, pre- and post- TICI reperfusion scores, and intracranial haemorrhage as defined by PH grading score for haemorrhage. Demographic and treatment factors were correlated with good functional outcome (mRS < 2 at 90 days and a comparison was made for patients undergoing angioplasty alone versus stenting. All patients who underwent carotid stent were placed on dual antiplatelet agents while angioplasty patients received aspirin only. Results: Twenty-four patients (15 males, 9 females; mean age, 67 years) satisfied the inclusion criteria. Seventeen patients underwent placement of carotid stent and 7 patients had angioplasty alone. Patients in both subgroups were comparable across characteristics including comorbidities, time for onset to recanalization, ASPECTS, and IV tPA use. 35% of patients who underwent stenting had good functional outcomes, versus 71% of patients treated with angioplasty alone, although these differences were not statistically significant. No differences were seen for the two treatment groups comparing time from onset to recanalization, baseline ASPECTS, and IV tPA use. Additionally, increased age (p = 0.049) and post-treatment parenchymal haemorrhage- PH1 or PH2 (p = 0.016) correlated with poor outcomes (mRS > 2). All parenchymal haemorrhages (6/17) and deaths (5/17) fell within the stenting subgroup (35.3% and 29.4%, respectively). Conclusions: This data suggest that patients undergoing angioplasty alone in the setting of acute internal carotid artery occlusion may have improved functional outcome at 90-day compared to those undergoing stenting. This study was limited by a small sample size and a larger study would be needed to confirm these findings. Keywords: angioplasty, stenting, acute ischemic stroke, carotid occlusion. Disclosures: O. Choudhri: None. M. Gupta: None. A. Feroze: None. G. Albers: None. M. Lansberg: None. H. Do: None. R. Dodd: None. M. Marcellus: None. M. Marks: None.